2019
DOI: 10.1002/adma.201807019
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Donor–Acceptor Terpolymers Toward High‐Efficiency Polymer Solar Cells

Abstract: The development of conjugated alternating donor–acceptor (D–A) copolymers with various electron‐rich and electron‐deficient units in polymer backbones has boosted the power conversion efficiency (PCE) over 17% for polymer solar cells (PSCs) over the past two decades. However, further enhancements in PCEs for PSCs are still imperative to compensate their imperfect stability for fulfilling practical applications. Meanwhile development of these alternating D–A copolymers is highly demanding in creative design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 212 publications
0
82
0
Order By: Relevance
“…Solution-processed polymer solar cells (PSCs) have become a focus of attention in the academic and industrial fields due to the great advantages of lightweight, potential low cost, flexibility, semitransparency, and the large-area fabricated devices. [1][2][3][4][5][6] The most common PSCs are fabricated using a bulk heterojunction (BHJ) architecture, where the crucial active layer is comprised of It is well known that the thieno [3,4-b]thiophene (TT) is a very important functional unit that has been extensively adopted in the PTB family donor polymers, which consist of alternating electron-rich benzo [1,2-b:4,5-b′]dithiophene (BDT) units and electron-deficient TT units, due to its stabilized quinoidal form. [28][29][30] Many previous reports have demonstrated that the existence of the TT unit can broaden the absorption band and extend the polymer absorption range to longer wavelength.…”
Section: It Is Of Great Significance To Develop Efficient Donor Polymmentioning
confidence: 99%
“…Solution-processed polymer solar cells (PSCs) have become a focus of attention in the academic and industrial fields due to the great advantages of lightweight, potential low cost, flexibility, semitransparency, and the large-area fabricated devices. [1][2][3][4][5][6] The most common PSCs are fabricated using a bulk heterojunction (BHJ) architecture, where the crucial active layer is comprised of It is well known that the thieno [3,4-b]thiophene (TT) is a very important functional unit that has been extensively adopted in the PTB family donor polymers, which consist of alternating electron-rich benzo [1,2-b:4,5-b′]dithiophene (BDT) units and electron-deficient TT units, due to its stabilized quinoidal form. [28][29][30] Many previous reports have demonstrated that the existence of the TT unit can broaden the absorption band and extend the polymer absorption range to longer wavelength.…”
Section: It Is Of Great Significance To Develop Efficient Donor Polymmentioning
confidence: 99%
“…According to the operation mechanism, to maximize the photovoltaic performance of PSCs, the design principles of efficient polymer donors should be under the following considerations: (1) achieve broad absorption spectra to adequately cover the incident solar spectrum, which is favorable for enhancing the number of absorbed photons, and further for increasing the short‐circuit current density ( J sc ) of photovoltaic devices; (2) provide a sufficient E HOMO and/or E LUMO energy offsets between the donor and acceptor materials to facilitate charge dissociation, and enlarge the gap between E LUMO of acceptor and E HOMO of donor to enhance the open‐circuit voltage ( V oc ); (3) control the morphology and aggregation behavior in blending with electron acceptors to ensure efficient carrier transport and suppressed charge recombination for further increasing the fill factor (FF) . Based on the concerns above, besides the synthesis of novel traditional π ‐conjugated D‐A alternative copolymers, the design of random terpolymers by chemically embedding a third component into copolymer backbones in a random way enabling a D 1 ‐A‐D 2 ‐A or D‐A 1 ‐D‐A 2 structure also provides a rational and facile approach to develop efficient polymer donors . By successfully introducing the third unit, the optical and electrochemical properties of the original copolymers could be easily adjusted.…”
Section: Introductionmentioning
confidence: 99%
“…Arrangement of an alternating donor (D) and acceptor (A) units in a conjugated system is a common approach for tuning the electronic properties. These D−A materials are widely used to design advanced and emerging optoelectronic devices ( Dang et al., 2019 ; Kanimozhi et al., 2012 ; Yang et al., 2008 ; Bronstein et al., 2011 ; Steckler et al., 2009 ). Although it is commonplace to design, synthesize, and characterize linear π-conjugated D−A oligomers and polymers, very few instances exist for using D−A motifs to design π-conjugated macromolecules with the ring topology.…”
Section: Introductionmentioning
confidence: 99%